Penerapan Restorative Justice Dalam Kasus Kecelakaan Lalu Lintas Studi Putusan Nomor : 7/Pid.Sus-Anak/2020/Pn Pnj) - Jayenov Isak; Rizkan Zulyadi; M. Citra Ramadhan (Mahesa Research Center, 2023)
This article aims to analyze the concept of restorative justice in the perspective of criminal law in Indonesia, judges' considerations and the application of restorative justice in traffic accident cases. The case that is the focus of the author is the application of restorative justice in solving traffic accident cases in Samarinda City. in decision number 7/Pid.Sus-Children/2020/PN Pnj. The type of research that the authors use in this study is empirical juridical. Empirical law research is an unwritten positive legal research regarding the behavior of community members in social relations. The results of the study state that the concept of restorative justice. The criminal justice system is a system in society for managing crime. Its main aim is to prevent the Consensus agreement from being actually nothing new to Indonesian society. Considering, that children who are in conflict with the law are not miniature adults who must be fully responsible for their actions, but children who commit crimes must have their rights protected, they must be restored to become children of the nation who have a future as the hope of the nation.